The evolution of radiobiology through the work of women scientists: the work of Christiane Ferradini. (4th March 2022) - Stuart, Marilyne; Houée-Levin, Chantal
Abstract: Purpose: Pay tribute to Christiane Ferradini and highlight the importance of her work as a scientist. Conclusions: Christiane Ferradini was born in 1924 in the south of France. She graduated from the Paul Sabatier University in Toulouse, France. In 1947, she joined the Curie Laboratory of the Radium Institute (which was then under the leadership of Madame Irène Joliot-Curie) to pursue her doctoral research. After her defence in 1955, she commenced her journey dedicated to the advancement of science. She became an exceptional teacher. She led a research group that contributed, through many fruitful collaborations, to the opening of a new chapter in radiation biology and medicine. Together they shed light on free radical formation and their reactions with biomolecules. Christiane published a total of 190 scientific articles and 9 books. She died in 2002.